MEMAHAMI PEMAKNAAN KELUARGA ALTERNATIF DALAM ANIME SPY X FAMILY - Nandya Finandika; Hapsari Dwiningtyas Sulistyani; Primada Qurrota Ayun (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Family is often used as a topic of discussion in the media, especially movies. So that it will indirectly form a dominant ideology regarding the concept of family represented in the film. The conception of family in films generally emphasizes the concept of a nuclear family based on heterosexual couples with dominant attributes attached to it so that families outside of this thinking can be marginalized. This research will examine how alternative families in the anime Spy x Family that have been contextualized in a queer context are represented. The purpose of this research is to see how this anime depicts alternative families. This research uses Roland Barthes' semiotic analysis method. The analysis consists of two levels, namely denotative, connotative, and myth, which are used to see the meaning in the Spy x Family anime scene. This research uses queer theory as a framework but in order to show the form of heterosexual performativity in families that offer alternatives beyond that. The results of this study indicate that the alternative family shown in the Spy x Family anime is a form of family that is classified as queer because the family in this anime is formed on the basis of bonds of interest and the division of family roles that are not based on gender or sexuality. However, the alternative family is not fully categorized as queer. The family in the Spy x Family anime still contains some dominant concepts such as the gradual growth of emotional bonds and the division of roles that slowly follow heteronormative rules. The father's role is shown as a superior figure so that the father has an important role in almost every aspect of the family. Meanwhile, the mother's role tends to be shown in a more passive manner where this anime displays the mother's fear and worry of not being able to meet the standards of mothers in general who are known to be feminine. Through this, it also indirectly shows that this alternative family still contains a deep-rooted patriarchal culture in it. The role of children is also still in the dominant thinking where children are tasked with learning and helping parents. The existence of pets that are considered as family also still shows that the family in the Spy x Family anime is still in the dominant concept because it carries the humanization of animals which is normal in today's families. So, it can be concluded that the alternative family in the Spy x Family anime is still trapped in the thinking of the dominant family so that the family's alternativeness begins to fade and follows the rules of the dominant family.